A Review of Physicochemical Properties influencing Vidarbha’s Freshwater Ecosystems - Shital Goswade; N. Wadhave (International Journal of Scientific Research in Science and Technology, 2026)
Freshwater ecosystems, mainly lakes contain vital natural resources that support ecological balance, human livelihoods, agriculture and regional water in Vidarbha region of Maharashtra. The quality and sustainability of these aquatic systems are primarily governed by their physicochemical characteristics, which determine water usability for household, agriculture and other purposes (APHA, 2017; Wetzel, 2001). Freshwater ecosystems in Vidarbha represent dynamic environments where key physicochemical parameters such as temperature, pH, dissolved oxygen (DO), chemical oxygen demand (COD), turbidity, electrical conductivity and nutrient concentrations significantly influence water quality and aquatic life (APHA, 2017; Wetzel, 2001). Variations in these parameters are driven by both natural processes and human origin activities, including agriculture runoff and urbanization. (Chapman, 1996). Understanding and monitoring these physicochemical properties is therefore basic need for assessing water quality, ensuring sustainable management of freshwater resources. Present review highlights the condition of freshwater ecosystems of vidarbha through physicochemical analysis.
Keywords: Ecosystem; Vidarbha; physicochemical and urbanization